The Influence of Organizational Culture, Principal Leadership, Digital Literacy, and Work Motivation on Teacher Integrity - Dinda Putri Rezeki; Mesiono Mesiono; Khadijah Khadijah (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
Teacher integrity has become an essential foundation of educational professionalism in responding to ethical and technological challenges in the digital era. This study aimed to analyze the direct and indirect effects of organizational culture, principal leadership, digital literacy, and work motivation on teacher integrity. The study employed a quantitative survey approach involving 209 public senior high school teachers selected through multistage sampling. Data were collected using validated and reliable questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings revealed that organizational culture directly affected teacher integrity (β = 0.530) and work motivation (β = 0.386), while digital literacy directly influenced teacher integrity (β = 0.304) and work motivation (β = 0.788). Principal leadership significantly affected work motivation (β = 0.319), and work motivation directly influenced teacher integrity (β = 0.795). Furthermore, work motivation mediated the effects of organizational culture, principal leadership, and digital literacy on teacher integrity. This study contributes to the development of an integrated teacher integrity model and recommends strengthening ethical organizational culture, leadership quality, digital competence, and teacher motivation to improve educational professionalism.